Liquefaction features at an archaeological site: Investigations of past earthquake events at the Early Christian Basilica, Ancient Lechaion Harbour, Corinth, Greece - Pavlopoulos, Kosmas (2015)
A synthesis of investigations carried out at the archaeological site of the Early Christian Basilica, located in the ancient harbour of Lechaion, Corinth, Greece in order to study the origin and triggering mechanism of deformation structures observed on the temple floor, is presented. These surface structures are indicative of earthquake induced ground liquefaction and their relationship with the subsurface soil stratigraphy and structure is examined. Investigations of stratigraphic data from archaeological excavations conducted from 1956 to 1965 provide indications of artificial fill deposits overlying a sandy-gravelly substratum. Geophysical survey of EM, GPR and ERT provided further information regarding the substratum properties/stratigraphy of the site indicating subsurface fissures and lateral spreading trends that are in agreement with the surface deformation structures. Lithostratigraphic data obtained from four vibracores drilled in the southern aisle of the temple, suggest estuarine deposits of coarse sand to fine gravel with grain size properties indicative of layers with high liquefaction potential. The results of the study, suggest at least three seismic events that induced ground liquefaction at the site. The first event pre-dates the construction of the Basilica, when Lechaion harbour was in operation. The second event post-dates the construction of the Basilica potentially corresponding to the regionally damaging A.D. 524 earthquake, followed by the third event, that commensurate with the A.D. 551 earthquake and the destruction of the temple. © 2015 Elsevier B.V.